Adaptive finite‐time control for output regulation of nonlinear systems with completely unknown control directions. (25th March 2021) - Jia, Fujin; Lu, Junwei; Li, Yongmin
Abstract: This article studies the finite‐time output regulation problem for nonlinear strict‐feedback systems with completely unknown control directions and unknown functions. First, according to the necessary conditions for the solvability of the output regulation problem, the output regulation problem of nonlinear strict‐feedback systems and the external system is transformed into a stabilization problem of nonlinear systems. Second, an internal model with external signals is designed. Third, based on finite time, fuzzy control, output feedback control, and Nussbaum gain functions, the control law is designed so that all signals of the closed‐loop system are the semi‐global practically finite‐time stable (SGPFS), and the tracking error converges to a small neighborhood of the origin in a finite‐time. Finally, the proposed algorithm is applied to the finite‐time tracking problem of Chua's oscillator system.